Piecing Together Large Polycyclic Aromatic Hydrocarbons and Fullerenes: A Combined ChemTEM Imaging and MALDI-ToF Mass Spectrometry Approach - Gover, R. K. E.; Chamberlain, T. W.; Sarre, P. J.; Khlobystov, A. N. (Frontiers in Chemistry, 2021)
Motivated by their importance in chemistry, physics, astronomy and materials science, we investigate routes to the formation of large polycyclic aromatic hydrocarbon (PAH) molecules and the fullerene C60 from specific smaller PAH building blocks. The behaviour of selected PAH molecules under electron (using transmission electron microscopy, TEM) and laser irradiation is examined, where four specific PAHs – anthracene, pyrene, perylene and coronene – are assembling into larger structures and fullerenes. This contrasts with earlier TEM studies in which large graphene flakes were shown to transform into fullerenes via a top-down route. A new combined approach is presented in which spectrometric and microscopic experimental techniques exploit the stabilisation of adsorbed molecules through supramolecular interactions with a graphene substrate and enable the molecules to be characterised and irradiated sequentially. Thereby allowing initiation of transformation and characterisation of the resultant species by both mass spectrometry and direct space imaging. We investigate the types of large PAH molecule that can form from smaller PAHs, and discuss the potential of a ‘bottom-up’ followed by ‘top-down’ mechanism for forming C60.